Recommended Cleaning Practices for Cell Phones in the Operating Room: A Modified Scoping Review - Dowden, Alexa; Manson-Brick, Nori; Martin, Wanda; McKerricher, Leah; Wiebe, Mackenzie (Operating Room Nurses Association of Canada Journal, 2020)
Cell phone use among operating room (OR) personnel is increasingly common. Cell phones in the operating room can have high levels of bacterial contamination, with the potential to lead to increased risk for surgical site infections (SSI). No universally accepted guidelines exist for cleaning or disinfecting cell phones in the OR. The authors completed a modified scoping review of eight articles to examine researched cleaning practices for cell phones in the OR. Cleaning protocols and products differed among the studies, but each type of cell phone disinfection showed significantly decreased bacterial load especially when combined with proper handwashing. There is a need for more research to determine specific evidence that can guide future policy and nursing practice for cleaning cell phones in the OR.